Assessment of efficacy of pesticides applied singly and in combination on rice sheath blight disease development - H. RAJASHEKARA, PRATIBHA SHARMA; U.D. SINGH, G. PRAKASH*, R.T.P. PANDIAN (Indian Phytopathology, 2015)
Efficacy of commonly used pesticides namely carbendazim (0.1%), hexaconazole (0.1%), endosulfan (0.042%), chlorpyriphos (0.02%), thiobencarb (0.3%) and butachlor (0.4%) applied singly and in combination were evaluated against rice sheath blight (Rhizoctonia solani), during kharif 2010 and 2011 under pot culture conditions. Among the various pesticide combinations, carbendazim (0.1%) applied along with endosulfan (0.042%) was found to be the most effective against sheath blight, where the lowest mean disease severity was 17.36% and the relative vertical spread (RVS) was Â 4.18%. This combination increased the grain yield and straw yield by 85.68% and 111.73%, respectively in comparison to R. solani inoculated control without any pesticide. This was followed by hexaconazole (0.1%) combined with endosulfan (0.042%), where the mean disease severity was 19.84% and the relative vertical spread was 16.34%. It increased the grain yield by 72.21% and straw yield by 104.37% when compared to R. solani inoculated control without any pesticide. In case of individual application of carbendazim, the mean disease severity and relative vertical spread were observed to be 24.81% and 22.37%, respectively. Per cent increase in grain yield and straw yield were recorded as 29.86% and 61.94%, respectively. Treatment with hexaconazole alone reduced the mean disease severity up to 27.71% and relative vertical spread of 25.06%. It increased grain yield up to 28.10% and straw yield up to 60.35%. Thus, it is evident that, combined application of pesticides not only shows higher efficacy in controlling the disease, but also increases grain yield and straw yield.